PENELANTARAN ANAK PASCA PERCERAIAN MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 (Studi Kasus: Desa Bantayan Kecamatan Simpang Ulim Kabupaten Aceh Timur) - Hadi, M Naufal; Zubaidi, Zaiyad; Mustaqim, Riza Afrian (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to determine the factors of child neglect after divorce, review legal protection based on Law Number 35 of 2014 concerning Child Protection, and identify solutions and prevention of such cases in Bantayan Village, Simpang Ulim District, East Aceh Regency. This study uses a normative-empirical legal approach, with qualitative methods and data collection techniques through interviews, observations, and documentation of child victims, caregivers, and village officials. The results of the study indicate that the main factors of child neglect after divorce include economic problems, parental remarriage, parents who migrate and lose contact, lack of responsibility and communication between parents, and minimal intervention from the village government or related institutions. Based on Law Number 35 of 2014 Article 26 paragraph (1), it was found that children's rights to care, protection, and education were not fulfilled. Reviewed from the Best Interest of the Child theory by John Eekelaar, the condition of these children does not reflect the fulfillment of the child's best interests. Therefore, an active role is needed from all parties to prevent and handle similar cases, including through increasing legal awareness and collaboration between village governments and child protection agencies.